(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Vaginal discharge is the commonest concern among women and leads many women to visit Gynaecology OPD. It is a normal part of women reproductive cycle, unless it causes itching, burning or other bothersome symptoms. Association between vaginal discharge and reproductive tract is weak. Psychological factors also contribute in vaginal discharge. So the problem of vaginal discharge can be best understood not only in bio-medical perspective but also in socio-cultural perspective. Proper understanding of the subject is required for appropriate medical intervention and bringing awareness among women. Objectives: To determine prevalence of vaginal discharge, the socio-demographic factors associated with it, women’s perceptions of vaginal discharge and their treatment seeking behaviour. Materials and Methods: This cross sectional study was performed at outpatients’ Department of Obstetrics and Gynecology, Combined Military Hospital, Chattogram from January 2016 to January 2017. Total 150 women with complains of vaginal discharge were interviewed with questionnaire. Results: Most of the patients63(42%) belong to 25-34 age group, 86(57.3%) had poor sanitation facilities and 126(84%) used cloth pads during menstrual period. Many of them had backache 64(42.6%) followed by itching, bad smell 48(32%) and lower abdominal pain 15(10%). Most of the cases 98(65.3%) were multiparous. Conclusion: To diminish the problem of vaginal discharge women should improve their health knowledge, empower economic status, maintain personal hygiene. Further study is needed for better outcome. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 183-185